A Proposed Keyword Taxonomy for Operations Management Research - Juan A. Marin-Garcia; Julien Maheut; Pilar I. Vidal-Carreras (Journal of Industrial Engineering and Management)
Purpose: To develop a controlled vocabulary of less than 30 terms that represents level 1 of a taxonomy for the field of operations management, integrating previous available work to improve efficiency in searching and retrieving scientific information in the area.